Natural Shaping of Acellular Dermal Matrices for Implant‐Based Breast Reconstruction via Expansile Kirigami. Issue 6 (19th December 2022) - Lee, Young‐Joo; Kanchwala, Suhail K.; Cho, Hyesung; Jolly, Jason Christopher; Jablonka, Eric; Tanis, Michael; Kamien, Randall D.; Yang, Shu
Abstract: To complete a successful and aesthetic breast reconstruction for breast cancer survivors, tissue reinforcing acellular dermal matrices (ADMs) are widely utilized to create slings/pockets to keep breast implants or autologous tissue transfer secured against the chest wall in the desired location. However, ADM sheets are 2D and cannot completely cover the entire implant without wrinkles. Here, guided by finite element modeling, a kirigami strategy is presented to cut the ADM sheets with locally and precisely controlled stretchability, curvature, and elasticity. Upon expansion, a single kirigami ADM sheet can conformably wrap the implant regardless of the shape and size, forming a natural teardrop shape; contour cuts prescribe the topographical height and fractal cuts in the center ensures horizontal expandability and thus conformability. This kirigami ADM can provide support to the reconstructed breast in the desired regions, potentially offering optimal outcomes and patient‐specific reconstruction, while minimizing operative time and cost. Abstract : An expansile kirigami acellular dermal matrix (ADM) offers natural shaping of implant‐based breast reconstruction with securely holding the implant. Guided by finite element modeling, stretchability, curvature, and elasticity of kirigami ADM is precisely controlled. The developed kirigami ADM potentially offers patient‐specific reconstruction while minimizing operative time and cost.